Reading and Interdisciplinary Thinking in Mathematics Class and Information Sciences - Pirela-Morillo, Johann (2017)
The objective of the work is to present a teaching experience through which actions were generated to foster interdisciplinary thinking between Mathematics and Information Sciences. The methodology used was based on the design of strategies supported by the reading of two texts, using as a technique the didactic systematization. This systematization was based on an interdiscursive matrix as an instrument for recording and analyzing information, in which relationships and meanings between texts were evidenced. The results revealed the activation of mechanisms for the complex and interdisciplinary appropriation of knowledge, and also the conception of reading as a tool to dominate intellectual processes from a dynamic approach. In conclusion, it is pointed out that intertextual exercises mobilize different types of knowledge to interact in today’s global environments.